Carotenoid contents in anoxygenic phototrophic purple bacteria, Marichromatium Sp. and Rhodopseudomonas Sp. of tropical environment, Malaysia - Khan Chowdhury, Ahmed Jalal; Zainal Abidin, Zaima Azira; Zainal Abidin , Nor Hafizah; Rahman, Mohammad Mustafizur; Yunus, Kamaruzzaman; Nordin, Noor Faizul Hadry (Oriental Scientific Publishing Co., 2014)

(untitled)
Carotenoids have shown extensive applications in pharmaceutical, aquaculture and animal feed industries. Recently, researchers have been studied on their potentiality for the health benefits in reducing the risk of cancer and neurodegenerative diseases. Based on above perspectives a study was conducted in tropical environment to evaluate the total carotenoid content, dry cell weight and bacteriochlorophyll type of phototrophic purple bacteria;Marichromatium sp. and Rhodopseudomonas sp. The bacteria Marichromatium sp. was isolated from the mangrove sediments, Kuantan Pahang. While, Rhodopseudomonas sp. was collected from fish rearing tanks INOCEM, IIUM. The bacteria were cultivated and monitored by using 112 media under anaerobic light conditions at 2500-lux light intensity of continuous illumination of 60-watt tungsten bulb at 30±2°C. Total carotenoid contents and dry cell weight of the bacterial cells were compared from day 0 to day 5 using UV-VIS spectrometer. Bacteriochlorophyll type was also determined using UV-VIS spectrometer. The results showed that isolate IIUM-JHR2 produced the highest total carotenoid content (4.08±2.21mg/g) at day 3 while IIUM-JHM1produced the highest dry cell weight (3.83±1.57 g/L) at day 2. Statistical analysis showed significance differences (p<0.05) in dry cell weight among the isolates but no significant differences (p>0.05) detected for total carotenoid contents among the species. However, live cell cultures exhibited absorption maxima at 382, 495.5, 524, 591, 806 and 864 nm in all isolates indicating the presence of bacteriochlorophylla and carotenoids belonging to the spirilloxanthin series. The finding reveals that these bacteria could be utilized in aquaculture as fish feed supplement to enhance growth, survival and coloration of cultured fishes. Furthermore, they can play significant role as potential elements towards food and pharmaceutical industries.